Observational studies of the effects of wind mixing and biological process on the vertical distribution of dissolved oxygen off the Changjiang Estuary - Miao, Yanyi; Wang, Bin; Li, Dewang; Sun, Xiangyu; Xu, Zhongsheng; Sun, Qianwen; Jiang, Zhibing; Ma, Xiao; Jin, Haiyan; Chen, Jianfang (Frontiers in Marine Science, 2023)
Wind mixing is important in regulating dissolved oxygen (DO) variability; however, the transect response of DO dynamics before and after wind disturbance has seldom been documented with field data. In the summer of 2017, repeat transect observations off the Changjiang Estuary were conducted throughout a fresh wind (9.8 m s–1) event to reveal the role of physical mixing and biological activity in DO variations. Generally, after the wind event, depth-integrated water column DO saturation increased by 9%–49% through physical diffusion with a weakened stratification and enhanced phytoplankton bloom. Thus, water column hypoxia was alleviated as the hypoxia thickness decreased from 30 m to 20 m. However, poorly ventilated bottom hypoxia aggravated with a further decrease in DO. In this case, the physical water mass mixing by transporting DO downward had a limited contribution to the water-column DO budget, while upwelled nutrients induced by mixing fueled the extended vertical area of algae bloom and subsequent substantial oxygen consumption. As the wind speed increased, the air-sea exchange would be important in supplying DO, especially in nearshore areas, which can effectively offset the DO deficiency. In summary, frequently occurring fresh wind-mixing events off the Changjiang Estuary would alleviate hypoxia in the water column but probably exacerbate hypoxia at the bottom, as determined by competing ventilation and respiration roles. Such complex interactions likely occur and perform differently as wind stress varies. Thus, high-spatial and long-term process observations are required to better understand the net effects of bottom hypoxia evolution.